2015
DOI: 10.1016/j.jbi.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Improving diagnostic accuracy using EHR in emergency departments: A simulation-based study

Abstract: It is widely believed that Electronic Health Records (EHR) improve medical decision-making by enabling medical staff to access medical information stored in the system. It remains unclear, however, whether EHR indeed fulfills this claim under the severe time constraints of Emergency Departments (EDs). We assessed whether accessing EHR in an ED actually improves decision-making by clinicians. A simulated ED environment was created at the Israel Center for Medical Simulation (MSR). Four different actors were tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 69 publications
0
37
0
Order By: Relevance
“…One solution implemented for research purposes is a simulated ED in which ED physicians are asked to use the EHR system in a set of typical cases. One such study has shown that using EHR reduces diagnosis mistakes, saves time and increases physicians' confidence level [82].…”
Section: Ehr and Emergency Department Performancementioning
confidence: 99%
See 1 more Smart Citation
“…One solution implemented for research purposes is a simulated ED in which ED physicians are asked to use the EHR system in a set of typical cases. One such study has shown that using EHR reduces diagnosis mistakes, saves time and increases physicians' confidence level [82].…”
Section: Ehr and Emergency Department Performancementioning
confidence: 99%
“…System use was more frequent on crowded days. Ben-Assuli et al [82] Track-log file database analysis Viewing medical history via EHR and using an HIE system was associated with a reduction in single-day admissions and the rate of readmission within seven days. Overhage et al [104] Randomized controlled trial No effect of using an electronic patient records system on admission rate or repeat visits was found.…”
Section: Authorsmentioning
confidence: 99%
“…• Improved decision making 13 • Improved workflow 14,15 • Improved sourcing and documenting of a patient's history 3,16…”
Section: Resultsmentioning
confidence: 99%
“…1,3, 11,13,16 It has been documented that the transition of care across multiple health care providers can be better coordinated through EHR use. 14,25 EHR clinician use is particularly motivated by repeat and complex patients who present to the ED. 25 Therefore, a single sign-on to My Health Record from the ED clinical information system was considered a critical success factor for use.…”
Section: Benefits Of My Heath Record In the Emergency Departmentmentioning
confidence: 99%
“…Almost all the medical complaints, diagnoses, processes of clinical care, laboratory results, and medication use from various departments of most domestic hospitals are readily available from EMRs. The immediate accessibility of patient information is likely to help healthcare professionals improve patient care delivery and enhance the quality of medical decision-making [3,4]. Moreover, the development of integrated clinical decision support systems and EMRs has achieved substantial success in reducing medical errors and improving patient safety [5].…”
Section: Introductionmentioning
confidence: 99%